Investigation of microwave attenuation and shielding performance of PTFE/Fe2O3/OPEFB composites at X-band frequency - Bello, M. A.; Azis, R. S.; Shabdin, M. K.; Osman, N. H.; Yakubu, A. (Virtual Company of Physics, 2023)
This study explored the microwave attenuation and shielding properties of PTFE/Fe2O 3/OPEFB composites in the X-band frequency range. Fe 2O 3 nanoparticles were incorporated into the PTFE/OPEFB matrix using a powder-dry mixing technique. The composites were characterized using XRD and FESEM, and attenuation performance was evaluated using a VNA. The results indicated that the addition of Fe 2O 3 nanoparticles improved microwave attenuation and shielding properties, with the composite containing 15 wt Fe2O 3 exhibiting the highest attenuation of 16.02 dB. The homogeneous dispersion of Fe2O3 nanoparticles was confirmed through FESEM analysis, and XRD analysis confirmed the presence of Fe2O 3 nanoparticles in the composites. The study concludes that PTFE/Fe2O 3/OPEFB composites have potential for electromagnetic interference shielding applications in aerospace, telecommunications, and electronics industries.